The histopathological prevalence of malignant catarrhal fever in swamp buffaloes slaughtered in the private slaughterhouses in Bogor district - Damayanti, Rini (Indonesian Journal of Animal and Veterinary Sciences, 1995)
Surveys were conducted in five private slaughterhouses in Bogor district to reveal the histopathological prevalence rates of malignant catarrhal fever (MCF) cases in buffaloes . The study was carried out from 1992-1994 in five sub-districts, namely: Ciawi, Caringin, Cijeruk, Megamendung and Cisatua, covering 47 villages . Thirty- two samples (18 .1%) from a total of 177 were histologically being positive for MCF, although the distribution and the severity of lesions were varied amongst them . From those 32 cases examined, lesions observed in the rete mirabile, lung, kidney, liver, urinary bladder, spleen, abomasum, heart, and small intestine were as follows : 84.4%, 77 .3%, 65 .6%, 53 .1%, 28.196, 18 .8%, 9 .4%, 9 .1%, and 3.1% respectively. Keywords : Malignant catarrhal fever, swamp buffalo, prevalence, lession distribution, histopathology